The Effect of Sustainability Report, and Capital Structire On The Value of The Company with The Size of The Company As A Coding Variable - Lestari, Reni; Dwi Astuti, Christina (Green Publisher Indonesia, 2023)
This study examines the factors that influence firm value in companies listed on the Indonesia Stock Exchange. These factors are sustainability-occurrence, capital structure and company size as moderating variables. The population used in this study are companies from the energy sector, the non-cyclical consumer sector, the industrial sector, and the raw material sector on the Indonesia Stock Exchange in 2019 - 2021. The sample used in this research is 114 data that match the criteria. The sampling method used purposive sampling. Based on the results of research and tests conducted on 114 sample data from 2019 to 2021, it can be interpreted that sustainability reports have a positive effect on firm value, capital structure has a negative effect on firm value, but company size can strengthen the effect of sustainability reports on firm value. Meanwhile, the capital structure variable has no effect on firm value and firm size can strengthen the relationship between sustainability reports and firm size on firm value